THE TWO-WAY PROTECTIVE REGIME OF INTANGIBLE CULTURAL HERITAGE IN ARMED CONFLICT : APPLICATION OF MODERN LAWS IN AMALGAMATION WITH EARLIER VEDIC TRADITIONS. - Saini, Shivesh (Indonesia Law Review, 2023)
The destruction of property has been dealt with in different conventions across International Humanitarian Law. These regulations, however, demand more clarity in light of constantly evolving warfare methods. One such aspect is the protection of digital intangible assets in several forms of armed conflict. The existing protection conferred to intangible assets is questionable and has been very little addressed in light of international law in contrast with tangible assets. Therefore, the paper seeks to demonstrate the enforceability of existing principles over intangible assets. In addition, there is explicit dependability of protection of these intangible cultural assets on cyber security. The cyber technology of contemporary times is abundantly capable to affect the social and cultural assets of the opponent adversely. Recognizing the paradigm shift, the paper entails the comprehensive efforts that should be realized to expand the applicability of international law. Concerning this, the response of the international regime mainly rests on the material aspects neglecting the spiritual aspect that could assist in safeguarding the intangible cultural assets. In this direction, the later part of the paper is concerned with the religions of the Indian-sub continent i.e. Hinduism in the Asian context. Its objective is to draw inspiration from multiple social and legal norms to further the cause of safeguarding the intangible heritage that has been disregarded for a long time. The article sought to demonstrate that cultural laws and traditions are well-equipped and more adequate in protecting the digital manifestation of these intangible assets.